Product characteristics influence in consumer decision making process: a study at canned food department, Hankyu Jaya Bangsar / Ghazali Shamsuddin - Ghazali, Shamsuddin (Faculty of Business and Management, 1998)
Canned food department is one of several departments in any supermarket besides non food, fruit and vegetable, meat, seafood, household and dairy. I t s merchandise consists of sauce and flavour, cooking oil, spice, baking needs, canned food and vegetables, titbits, preservatives, biscuits, cordial, fruit juice, soft drinks, Confectionery, milk, beverages and breakfast cereals. This section can be considered as core department. Since most supermarkets including MHJ Bangsar, ore more emphasised on pricing and promotion strategy, they either conscious or not ignored the basic but important element in marketing - understand consumer behaviour.